Experiences of in-patient mental health services: systematic review. (21st March 2019) - Staniszewska, Sophie; Mockford, Carole; Chadburn, Greg; Fenton, Sarah-Jane; Bhui, Kamaldeep; Larkin, Michael; Newton, Elizabeth; Crepaz-Keay, David; Griffiths, Frances; Weich, Scott
Abstract : Background: In-patients in crisis report poor experiences of mental healthcare not conducive to recovery. Concerns include coercion by staff, fear of assault from other patients, lack of therapeutic opportunities and limited support. There is little high-quality evidence on what is important to patients to inform recovery-focused care. Aims: To conduct a systematic review of published literature, identifying key themes for improving experiences of in-patient mental healthcare. Method: A systematic search of online databases (MEDLINE, PsycINFO and CINAHL) for primary research published between January 2000 and January 2016. All study designs from all countries were eligible. A qualitative analysis was undertaken and study quality was appraised. A patient and public reference group contributed to the review. Results: Studies (72) from 16 countries found four dimensions were consistently related to significantly influencing in-patients' experiences of crisis and recovery-focused care: the importance of high-quality relationships; averting negative experiences of coercion; a healthy, safe and enabling physical and social environment; and authentic experiences of patient-centred care. Critical elements for patients were trust, respect, safe wards, information and explanation about clinical decisions, therapeutic activities, and family inclusion in care. Conclusions: A number of experiences hinder recovery-focused care and must be addressed with the involvement of staff to provide high-quality in-patient services. Future evaluations of service quality and development of practice guidance should embed these four dimensions. Declaration of interest: K.B. is editor of British Journal of Psychiatry and leads a national programme (Synergi Collaborative Centre) on patient experiences driving change in services and inequalities.